Usage of Social Media and Internet in Indian Elections: - (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Nowadays social media is becoming the battlefield for India's political parties. It's becoming a vital part of campaigning. The political parties form their own social media teams and generate content that propagates such as cartoons, memes etc. This field has also become an instrument for ordinary people to voice their concerns. Use of social media is also growing rapidly with the increasing use of smartphones. In a Democracy, media plays the most important role and keeps the Government active. With the advent of social media including Twitter, Facebook, WhatsApp, YouTube etc., the way campaigns are run in Politics has dramatically changed. Indians are classified as among the world's most active social media users. In India we saw the new trend in Indian politics during the 16th Lok Sabha election held in 2014. In deciding which party wins the most seats, social media played a proactive part. The Internet in India offers people opportunities to take part in interactive social media campaigns and become political activists. Offensive online behavior on social media pages occasionally poses potential threats to its users. Comments sometimes contain misunderstandings. The use of it as a mere campaign tool won't be very effective. But if used as a platform to share the government's latest decisions and effectively utilized for active citizen engagement, social media will show positive results for future Indian elections. Also, social media has become one of the important tools for almost all the political movements around the world. Spreading one's ideology, or at least getting it to reach more ears, can be a potent weapon. Social media has made democracy more inclusive, nothing to hide from.